(untitled) (e-Journal of Linguistics, 2019)
Quite a lot of approaches have been utilized to study humor texts; yet, none has been from an ecolinguistics’ perspective. This article specifically intends to scrutinize a particular humor text from Papua called mob on the ground of dialectical ecolinguistics as developed by Bang, Door, et al. (1993). The main purpose of this article is to describe the elements of core contradictions (i.e. race, age, sex, class, authority, ideology, town-country, private-public, and culture-nature) found in mob. The result of the analysis shows that all the nine elements of the core contradictions in mob are found in the bio-logics dimension indicating that the bio-logics dimension is the most dominant dimension in the world of the mob owners (i.e. the people of Papua).